2021
DOI: 10.1007/s40119-021-00217-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Telmisartan on Blood Pressure Control in Hypertensive Patients in India: A Real-World Retrospective Study from Electronic Medical Records

Abstract: Introduction: The effectiveness of telmisartan has been reported in Indian clinical trials; however, real-world data are limited. We aimed to provide real-world evidence regarding the effectiveness of telmisartan as monotherapy or in combination with other antihypertensive drugs (AHDs) in Indian patients with essential hypertension. Methods: Electronic medical record data of adult patients diagnosed with essential hypertension (C 140/90 mmHg) and who were prescribed telmisartan as mono-or add-on therapy were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Telmisartan is also an effective BP-lowering agent when given alone or in combination during day-to-day practice for Asian hypertensive patients with comorbidities like diabetes or dyslipidemia. [ 27 ] Effectiveness of telmisartan in diabetics is also supported by one animal study which shows that telmisartan works through voltage-dependent potassium channel also. [ 28 ] …”
Section: Discussionmentioning
confidence: 91%
“…Telmisartan is also an effective BP-lowering agent when given alone or in combination during day-to-day practice for Asian hypertensive patients with comorbidities like diabetes or dyslipidemia. [ 27 ] Effectiveness of telmisartan in diabetics is also supported by one animal study which shows that telmisartan works through voltage-dependent potassium channel also. [ 28 ] …”
Section: Discussionmentioning
confidence: 91%
“…24 Other studies have also suggested that ARBs have renoprotection and this effect of telmisartan appears to be stronger than Losartan, Candesartan, or Olmesartan in the early stage of DN patients. 25 There are also studies that show the results that creatinine is "significantly reduced by 18% from baseline (p<0.05). On the use of telmisartan 40 mg once daily for 12 months and the reduction was significantly greater than in the amlodipine group (p<0.05).…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 98%
“…Lipophilicity of the active molecule is essential for distribution in the body. 25 A recent meta-analysis of 20 randomized controlled trials of telmisartan performed primarily in diabetic patients concluded that telmisartan therapy may be effective in easing proteinuria or preventing its development. Telmisartan caused statistically significant reductions in percent change in urinary albumin/protein excretion and urinary albumin/protein to creatinine to telmisartan ratio relative to ARBs, AFIs, and other therapies by 20, 14, and 40%.…”
Section: Analysis Of the Use Of Antihypertensives Angiotensin Recepto...mentioning
confidence: 99%
“…This indicates that although there are many types of drugs for treatment of hypertension in China, the blood pressure compliance has not been significantly improved. The 2010 Chinese Guidelines for the Management of Hypertension proposes that effective management is key to prevention of serious cardiovascular and cerebrovascular complications [5,6].…”
Section: Introductionmentioning
confidence: 99%